THU0651 Should we reduce the dose of biological therapy to all patients with inflammatory arthritis achieving sustained therapeutic goal?. (15th June 2017) - Gonzalez-Alvaro, I; Sánchez-Piedra, C; Almodovar, R; Bachiller, J; Balsa, A; Blasco, AJ; Caliz, R; Candelas, G; Fernández-Carballido, C; García-Aparicio, A; García-Magallόn, B; García-Vicuña, R; et al.
Abstract : Background: Dose tapering of biological therapies (BT) in patients with rheumatoid arthritis (RA) or spondyloarthritis (SpA) is frequent in Spain. However, there is variability in BT optimization (BTO). So, Spanish Society of Rheumatology published in 2015 recommendations on how to optimize BT (1). Nevertheless, there is no solid evidence on which patient profiles BTO is appropriated. Objectives: To develop appropriateness criteria for BTO in patients with RA, axial SpA (axSpA) or peripheral SpA (pSpA) Methods: The RAND/UCLA appropriateness method was used. Five rheumatologists experienced in RA and/or SpA clinical research selected and defined the variables considered relevant when deciding reduction of BT in order to define patient profiles. Ten BT experienced rheumatologists anonymously rated 1 (completely inappropriate) to 9 (completely appropriate) each profile after reading evidence synthesis. Then, in a meeting, classification variables and profiles with disagreement were revised and all profiles were scored again. Profiles with a median score >6 were considered appropriate, those with a median score <3.5 were considered inappropriate and the remaining uncertain. In addition, a study of the prevalence of these profiles was performed in 9 Spanish hospitals. Results: Combining the options of variables 2, 304 different profiles were obtained for RA, 768 for axSpA, and 3, 072 for pSpA. 327 (14.2%) profiles in RA, 80 (10.4%) in axSpA, and 154 (5%) in pSpA were considered appropriate for BT dose reduction. By contrast, 749 (53.3%) profiles in RA, 270 (54.4%) in axSpA, and 1243 (54.5%) in pSpA were considered inappropriate. The remaining profiles were considered uncertain. In the preliminary study to determine profiles prevalence, we collected information from 242 RA, 171 axSpA and 172 pSpA patients that underwent BTO. We found that BTO was performed appropriately in 23% RA, 67% axSpA and 61% pSpA patients. BTO was indicated in uncertain profiles in 67% RA, 23% axSpA and 37% pSpA patients. Only in RA we detected BT dose reduction in patient profiles considered inappropriate (2%). Conclusions: Appropriateness criteria for BT dose reduction in three inflammatory conditions were developed and the preliminary prevalence study suggests that BTO was wiselly applied. However, further research in this field is needed to determine the real prevalence of clinical profiles of patients undergoing BTO in daily clinical practice and validate these criteria in real life. References: Gonzalez-Alvaro I et al. Rheumatology 2015; 54: 1200–1209. Disclosure of Interest: I. Gonzalez-Alvaro: None declared, C. Sánchez-Piedra Grant/research support from: Unrestricted grant from Abbvie, R. Almodovar: None declared, J. Bachiller: None declared, A. Balsa: None declared, A. Blasco Grant/research support from: Unrestricted grant from Abbvie, R. Caliz: None declared, G. Candelas: None declared, C. Fernández-Carballido: None declared, A. García-Aparicio: None declared, B. García-Magallόn: None declared, R. García-Vicuña: None declared, A. Gomez-Centeno: None declared, A. Ortiz: None declared, R. Sanmartí: None declared, J. Sanz: None declared, B. Tejera: None declared, I. Notario: None declared, M. Soto: None declared, C. Plasencia: None declared, V. Hernández: None declared, M. Espinosa: None declared, C. Ramos: None declared, P. Lazaro Grant/research support from: Unrestricted grant from Abbvie